Conjugate Additions to Vinyl-Substituted Aromatic N-Heterocycles - Klumpp, Douglas A. (Synlett, 2012)
Conjugate or Michael addition to vinyl-substituted aromatic N-heterocycles has been a useful synthetic method for the synthesis of functionalized heterocyclic compounds. A wide variety of heterocycles and nucleophiles undergo this chemistry. Recent work in this area has utilized transition-metal catalysts and some asymmetric synthesis has been accomplished. An overview of this chemistry is presented in this account.1 Introduction2 General Aspects3 Carbon-Centered Nucleophiles4 Nitrogen-Centered Nucleophile5 Oxygen and Sulfur Nucleophiles6 Transition-Metal-Catalyzed Reactions7 Asymmetric Conjugate Addition8 Summary and Outlook
Keywords: Michael addition; heterocycles; catalysis; nucleophilic addition; transition metals